Symbols of marginality in the biographies of religious and secular innovators: Jesus, Waldes, Booth, Kimbangu, Buddha, Mohammed and Marx - Droogers, André (Numen, 1980)
This article follows the path paved by Victor Turner and elaborates on the quasi-universal presence of marginal symbols in the biographies of religious leaders. While studying the boys' initiation ritual and other rites of passage among the Wagenia (Zaire), the author discovered the recurring presence of a number of symbols that indicated the temporal marginal position of persons undergoing the ritual, and was surprised to find that some of these symbols were also used in the biographies of religious innovators. These symbols may be present in the facts, but may also be of an artificial, constructed nature. The comparison is extended to the biography of a secular innovator: Marx.
Paid
Keywords: Booth; William; 1829-1912; Congo (Democratic Republic) – Religion; Gautama Buddha; Kimbangu; Simon; 1889?-1951; Liminality; Marx; Karl; 1818-1883; Muhammad; the Prophet; Peer reviewed; Symbolism in religion; Valdès; Pierre; 12th cent